Metformin-suppressed differentiation of human visceral preadipocytes: Involvement of microRNAs - Fujita, Koji (Int J Mol Med, 2016)
Visceral adipose tissue contributes to the pathophysiology of metabolic syndrome. Metformin has been reported to suppress lipogenesis in a murine preadipocyte cell line. However, the effect of metformin on the differentiation of human visceral adipose tissue remains unknown. MicroRNAs (miRNAs or miRs) have been suggested as therapeutic targets because of their involvement in the differentiation and maturation of fatty cells. The aim of this study was to determine whether metformin suppresses the differentiation of human preadipocytes and to identify miRNAs associated with the regulation of lipid metabolism. Human visceral preadipocytes (HPrAD-vis) were preincubated in growth media and then cultured with differentiation media containing metformin for 1 or 2 weeks. Adipogenic differentiation of the cells was assessed by Oil Red O staining, and soluble adiponectin in the culture media was measured using an enzyme-linked immunosorbent assay. Cell proliferation was assessed using a WST-8 assay, and the gene and protein expression of peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT-enhancer-binding protein α (C/EBPα) was determined by RT-qPCR and western blot analysis, respectively. miRNAs were profiled using human miRNA Oligo chips after total RNA was extracted and labeled. Oil Red O staining showed that metformin suppressed the accumulation of lipid droplets in HPrAD-vis cells. The adiponectin concentration in the culture media was also decreased in metformin-treated cells. The WST-8 assay revealed no effect on proliferation or growth inhibition following metformin treatment, although metformin suppressed the expression of PPARγ and C/EBPα. miRNA profiling further revealed differences between the metformin-treated group and control HPrAD-vis cells. Thus, the findings of the present study demonstrated that metformin suppressed the differentiation of human preadipocytes in vitro and altered the miRNA profile of these cells. Thus, the miRNAs whose expression levels were altered by metformin may contribute to the observed suppression of HPrAD-vis cell differentiation.